2019
DOI: 10.1371/journal.pone.0217225
|View full text |Cite
|
Sign up to set email alerts
|

Dutch ICU survivors have more consultations with general practitioners before and after ICU admission compared to a matched control group from the general population

Abstract: Background General Practitioners (GPs) play a key role in the healthcare trajectory of patients. If the patient experiences problems that are typically non-life-threatening, such as the symptoms of post-intensive-care syndrome, the GP will be the first healthcare professional they consult. The primary aim of this study is to gain insight in the frequency of GP consultations during the year before hospital admission and the year after discharge for ICU survivors and a matched control group from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
2
15
0
2
Order By: Relevance
“…Thus, a Dutch retrospective cohort study found an increased consultation rate in primary care following ICU discharge. 25 Considering that there were more than two million intensive care treatment cases just in Germany in 2017 26 and an assumed increase driven by the COVID-19 pandemic, 27 GPs need to know how to provide best postintensive care to these patients, as it…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a Dutch retrospective cohort study found an increased consultation rate in primary care following ICU discharge. 25 Considering that there were more than two million intensive care treatment cases just in Germany in 2017 26 and an assumed increase driven by the COVID-19 pandemic, 27 GPs need to know how to provide best postintensive care to these patients, as it…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a Dutch retrospective cohort study found an increased consultation rate in primary care following ICU discharge. 25 Considering that there were more than two million intensive care treatment cases just in Germany in 2017 26 and an assumed increase driven by the COVID-19 pandemic, 27 GPs need to know how to provide best postintensive care to these patients, as it has been already called for by others. 28 The concept of the PICS is quite recent, but GPs’ intensive care experiences may date back to medical studies or early hospital rotations.…”
Section: Introductionmentioning
confidence: 99%
“…Experiences with post-ICU follow-up clinics are reported [12], but insufficient evidence is available to determine whether ICU follow-up services are effective in identifying and addressing the unmet health needs of ICU survivors [13]. Since these patients do consult their general physician more frequently [14], it is essential to raise the awareness for PICS so that patients' ICU experiences are not merely a black box for their primary care physicians [15].…”
mentioning
confidence: 99%
“…Primary care providers should be able to screen for sequelae of PICS, PICS‐P, or PICS‐F and diagnose it if ICD‐10 codes exist, or be willing to refer patients to a psychiatric provider who could make the diagnosis. One recent study found ICU survivors who exhibit symptoms of PICS have more visits with primary care providers than patients with similar characteristics in the general population (van Beusekom et al, 2019).…”
Section: The Case For Icd‐10 Codesmentioning
confidence: 99%